CT imaging of myocardial perfusion and viability : Beyond structure and function - Bamberg, Fabian; Ruzsics, Balazs; Vliegenthart, Rozemarijn; Bastarrika, Gorka; Schoepf, U. Joseph (Medical Radiology, 2014)
The rapid evolution in cardiac computed tomography during the past decade has improved spatial and temporal resolution to the extent that cardiac CT is now an accepted alternative for the non-invasive interrogation of the heart. Beyond the assessment of cardiac structure and ventricular function, recent research has identified yet another promising CT application for the comprehensive diagnosis of coronary heart disease, namely the assessment of myocardial perfusion and viability. In this book, the first to be devoted to this novel application of CT, leading experts from across the world present up-to-date information and consider future directions. After short sections outlining the state of the art in the traditional applications of CT to image structure and function, the full range of CT techniques that may be employed to evaluate the myocardial blood supply are discussed in detail. Similarly, diverse CT approaches for the assessment of myocardial viability are described, with careful consideration of the available experimental and clinical evidence and the role of quantitative imaging.